Routledge handbook of Southeast Asian economics - Coxhead, Ian A. (Routledge, Taylor & Francis Group, 2015)
"Offers a new insight into the rapidly-developing picture of economics in Southeast Asia. The countries of the region display a great variety of development experiences. Its character is increasingly dominated by the region's ever-closer integration into the wider East Asian network of primary and secondary production and trade. A second striking feature of the Southeast Asia's development is the pace and extent of transformation of production and sources of household income. Since the 1980s the region as a whole has achieved and sustained a remarkable rate of growth, in the course of which tens of millions of its citizens have successfully escaped severe poverty. This handbook offers a timely and comprehensive overview of Southeast Asian economic development"--Resumé vydavatele